2011
DOI: 10.1124/dmd.111.038281
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of Isoflavone Conjugated Metabolites in Humans after Ingestion of Kinako

Abstract: ABSTRACT:Isoflavone aglycones daidzein (Dein) and genistein (Gein) are present primarily as glucuronides and sulfates in human plasma; however, very little is known about the plasma pharmacokinetics of isoflavone conjugates after soy ingestion. The aim of this study was to investigate metabolism and disposition of the isoflavone conjugated metabolites glucuronide or sulfate or both after ingestion of kinako (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“…The similarities in T max values and variation in plasma concentrations observed between Te-7G-4 S and Te-7G were observed between Te-7S and tectorigenin. Similar pharmacokinetic data have been previously described for plasma concentrations of daidzein, genistein, and their conjugated metabolites in humans after Kinako administration [27]. These results suggest the differential biliary excretion and reabsorption of conjugated tectoridin metabolites and tectorigenin [35], and further study to compare biliary excretion and urinary excretion in bile duct-cannulated rats and control animals is needed to confirm the enterohepatic recirculation of the metabolites.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The similarities in T max values and variation in plasma concentrations observed between Te-7G-4 S and Te-7G were observed between Te-7S and tectorigenin. Similar pharmacokinetic data have been previously described for plasma concentrations of daidzein, genistein, and their conjugated metabolites in humans after Kinako administration [27]. These results suggest the differential biliary excretion and reabsorption of conjugated tectoridin metabolites and tectorigenin [35], and further study to compare biliary excretion and urinary excretion in bile duct-cannulated rats and control animals is needed to confirm the enterohepatic recirculation of the metabolites.…”
Section: Discussionsupporting
confidence: 84%
“…The same pathways were also demonstrated in the metabolism of daizein, genistein, and quercetin glucosides after their oral intake in humans [25][26][27]. Thus, tectoridin undergoes extensive conjugation to produce its glucuronide, sulfate, and glucuronide-sulfate bis-conjugate in the body after hydrolysis by intestinal flora.…”
Section: Discussionsupporting
confidence: 52%
“…However, in pharmacokinetic studies, IF concentrations in urine are usually very high. Therefore, urine samples have to be diluted [24][25][26]. We investigated the matrix effect in the same blank urine samples after diluting these 10 times with water.…”
Section: Recovery and Matrix Effectmentioning
confidence: 99%
“…Recently, several studies have reported the metabolism of puerarin and daidzin [3,[15][16][17][18]. Luo et al [15] have reported that glucuronidation is the major metabolic pathway for puerarin when rats were given puerarin intravenously.…”
Section: Introductionmentioning
confidence: 98%